YBEY is an essential biogenesis factor for mitochondrial ribosomes. Issue 17 (17th March 2020) - Summer, Sabrina; Smirnova, Anna; Gabriele, Alessandro; Toth, Ursula; Fasemore, Akinyemi Mandela; Förstner, Konrad U; Kuhn, Lauriane; Chicher, Johana; Hammann, Philippe; Mitulović, Goran; Entelis, Nina; Tarassov, Ivan; et al.
Abstract: Ribosome biogenesis requires numerous trans-acting factors, some of which are deeply conserved. In Bacteria, the endoribonuclease YbeY is believed to be involved in 16S rRNA 3′-end processing and its loss was associated with ribosomal abnormalities. In Eukarya, YBEY appears to generally localize to mitochondria (or chloroplasts). Here we show that the deletion of human YBEY results in a severe respiratory deficiency and morphologically abnormal mitochondria as an apparent consequence of impaired mitochondrial translation. Reduced stability of 12S rRNA and the deficiency of several proteins of the small ribosomal subunit in YBEY knockout cells pointed towards a defect in mitochondrial ribosome biogenesis. The specific interaction of mitoribosomal protein uS11m with YBEY suggests that the latter helps to properly incorporate uS11m into the nascent small subunit in its late assembly stage. This scenario shows similarities with final stages of cytosolic ribosome biogenesis, and may represent a late checkpoint before the mitoribosome engages in translation.